Independent Stardom : Freelance Women in the Hollywood Studio System. - Carman, Emily (Texas film and media studies series., 2015)
During the heyday of Hollywood?s studio system, stars were carefully cultivated and promoted, but at the price of their independence. This familiar narrative of Hollywood stardom receives a long-overdue shakeup in Emily Carman?s new book. Far from passive victims of coercive seven-year contracts, a number of classic Hollywood?s best-known actresses worked on a freelance basis within the restrictive studio system. In leveraging their stardom to play an active role in shaping their careers, female stars including Irene Dunne, Janet Gaynor, Miriam Hopkins, Carole Lombard, and Barbara Stanwyck challenged Hollywood?s patriarchal structure. Through extensive, original archival research, Independent Stardom uncovers this hidden history of women?s labor and celebrity in studio-era Hollywood. Carman weaves a compelling narrative that reveals the risks these women took in deciding to work autonomously. Additionally, she looks at actresses of color, such as Anna May Wong and Lupe V?lez, whose careers suffered from the enforced independence that resulted from being denied long-term studio contracts. Tracing the freelance phenomenon among American motion picture talent in the 1930s, Independent Stardom rethinks standard histories of Hollywood to recognize female stars as creative artists, sophisticated businesswomen, and active players in the then (as now) male-dominated film industry.